Cultural Dilemmas that Native-English Teachers face while working in Mexico - Alvarez, Alejandra (Trinity College (Dublin, Ireland). School of Education, 2020)
The dominance of English as the global language has played a significant role in the increasing trend of International English Teachers traveling to different countries to teach the language while also gaining experience living and working in a foreign country. Such cross-cultural experiences might bring about differences in expectations which can cause dilemmas between individuals. This study investigates Native-English Teachers experiences of cultural dilemmas while working in Los Cabos, Mexico. The research adopted a qualitative approach with data being gathered via semi-structured face-to-to face interviews. Three research questions guided the study: a) How do Native-English teachers interpret a cultural dilemma, b) What are Native-English teachers experiences of cultural dilemmas while working in private bilingual schools in Mexico, and c) How do they deal with these dilemmas? The research is framed within the theoretical framework of cross-cultural theories and explores the literature on migrant teachers’ experiences abroad in a range of context. Cross-cultural theories provide the framework for analysis for the study. The research findings indicate four areas where participants appear to experience cultural dilemmas, these are: differing expectations between teachers and parents regarding students’ learning, opposing views with school personnel concerning the way they approach time and time management, issues concerning respect, and not being able to communicate because of language differences. Furthermore, the study examined participants’ development of intercultural competence in adaptations people make. Cross-cultural theories and previous studies on migrant teachers’ experiences abroad contribute to a greater understanding of why these dilemmas arise when individuals decide to take on the challenge of working in a foreign country. This analysis further suggests that cultural dilemmas are more universal and may be applicable to teachers working in other national contexts. The findings of this study underline the need to create spaces where both local and foreign teachers can collaborate in professional communities in order to facilitate teachers with pedagogical and cultural adaptation, acknowledging the financial resources and incentives needed for such spaces and interaction to take place. Further research might explore a cross-national study involving other regions of the country in order to contribute to the generalization of the results.
Keywords: Education; Language Education